Learning Obstacle of Prospective Mathematics Teacher on Triangle Material (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
The objective study is to produce a description of the learning obstacle of prospective mathematics teachers on the topic of triangles through the problem-solving proses and answers written by students. This study used a descriptive qualitative method and involved students enrolled in a mathematics education study program at a university in Yogyakarta, with a total of 26 students. Data collection is done through written tests and interviews. Data analysis is carried out using a descriptive method, which involves data reduction, presentation, and drawing conclusions. The research results revealed that prospective teachers faced several learning obstacles when solving triangle problems, including ontogenic, epistemological, and didactical obstacles.